2022
DOI: 10.18860/planar.v2i0.1855
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Quercetin in Extracts and Herbal Products of Phyllanthus niruri by TLC Densitometry Method

Abstract: Phyllanthus niruri has many pharmacological activities such as antioxidant, anti-inflammatory and anticancer. Phyllanthus niruri has been widely developed from extracts into herbal products. The flavonoid quercetin became an analytical marker compound to ensure the quality of P. niruri extracts in the Indonesian herbal pharmacopeia II. This study aimed to determine the levels of quercetin in extract and herbal products using the TLC Densitometry method. TLC Densitometry method using chloroform: ethyl acetate: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Based on the test results in Table 4, the percentage of EPMC content in the Kaempferia galanga rhizome extract was 54.13%. According to the IHP II, the requirement for EPMC content in Kaempferia galanga rhizome extract is not less than 4.3%, so this study fulfills this requirement 14 . Several previous studies have shown that there is a difference in the percentage of EPMC content in Kaempferia galanga rhizome extract.…”
Section: Determination Of Epmc Content In Kaempferia Galanga Rhizome ...mentioning
confidence: 64%
See 1 more Smart Citation
“…Based on the test results in Table 4, the percentage of EPMC content in the Kaempferia galanga rhizome extract was 54.13%. According to the IHP II, the requirement for EPMC content in Kaempferia galanga rhizome extract is not less than 4.3%, so this study fulfills this requirement 14 . Several previous studies have shown that there is a difference in the percentage of EPMC content in Kaempferia galanga rhizome extract.…”
Section: Determination Of Epmc Content In Kaempferia Galanga Rhizome ...mentioning
confidence: 64%
“…The chromatographic fingerprint is one of the important parameters in the standardization of herbal medicines, which is a method for identifying and determining the content of marker compounds in each plant or herbal medicine to ensure quality and pharmacological activity 12,13 . Marker compounds are compounds or groups of compounds present in plants with or without pharmacological activity 14 . An ideal marker compound should be specific for one plant or available in sufficient quantity for assay.…”
mentioning
confidence: 99%